Analisis Pengaruh Kecerdasan Emosional Terhadap Kinerja Karyawan Melalui Kepuasan Kerja dan Stres Kerja Pada Bank Mandiri Regional VIII Surabaya - Kirono, Larasati Putri; Anwar, Muhadjir (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Background – Based on these data, it can be seen that the tendency to achieve sales volume targets as a performance target for PT credit card units. Bank Mandiri is stagnant or flat, but the achievement figure is still below the predetermined target value, namely still below 100%. Achieving targets that are still below 100% is a threat to Bank Mandiri's credit card unit because it reduces revenue and unit valuation when compared to other units. Apart from that, from the employee side, if the target achievement is below 100%, it will have an impact on the absence of incentives issued as rewards, which is feared will reduce employee motivation and satisfaction with the Bank Mandiri credit card unit. Aim – This research aims to examine the effect of emotional intelligence on performance by considering job satisfaction and job stress as mediators. Design/ Methodology/ Approach – Using a quantitative approach, this research involved 90 employees of Bank Mandiri Regional VIII Surabaya City. The data collected was analyzed using SmartPLS 3.5 software, with a focus on the relationship between emotional intelligence, employee performance, job satisfaction, and job stress. Findings – This research shows that 1) emotional intelligence has a positive effect on employee performance, 2) emotional intelligence has a positive effect on employee performance through job satisfaction, and 3) emotional intelligence has a positive effect on employee performance through work stress. Conclusion – Emotional intelligence in the workplace as a form of improving employee performance is basically a necessity for employees. However, emotional intelligence will cause employees to achieve job satisfaction and reduce work stress. Research implication – In connection with emotional intelligence, companies should be able to maintain and improve the optimistic attitude of employees to achieve success. In relation to job satisfaction, companies should pay attention to aspects of providing work according to the tasks and functions given. In relation to work stress, companies should be able to create a conducive climate within the company. Limitations – This research is supported by data from bank employees, especially Bank Mandiri. There is a possibility that other banks will also provide the same or different results, which thus requires additional justification to see this at other banks.